The effect of the PjBL learning model on PGSD student's ability in researching natural science - Nita Pratiwi; Haryanto Haryanto; Woro Tri Hastuti (Jurnal Prima Edukasia, 2021)
This research aims to get information about the effect of the PjBL learning model on PGSD students' ability to research ICT-based science research subjects. This research is an experimental study with a pretest-posttest control group design. The outreach population is all 6th-semester students of the ICT-based Science Research Program at Yogyakarta State University, and the sampling method uses Purposive Sampling. Data analysis uses a Variant Univariate Analysis T-Test on the significance level of 5%. The results showed that the project-based learning model increases positively and significantly towards students' ability and a significant difference of results towards students' ability between the group of students studying in the class with conventional methodology and PjBl methodology.